Analisis Kepatuhan Persyaratan Izin Mendirikan Bangunan: Studi Kasus Apartemen Royal Kedhaton Yogyakarta Berdasarkan Peraturan Daerah Kota Yogyakarta Nomor 2 Tahun 2012 - Ishaq Chairansyah, Muhammad; Indana Zulfa, Naila; Naiahadi Titania, Sabriana; Ramadhanal Ayani, M. Tegar; Fadly Rahmatullah, Chelsea (Adagium: Jurnal Ilmiah Hukum, 2025)
The Royal Kedhaton Apartment does not meet the requirements for obtaining an IMB and the requirements for a building to be built in a cultural heritage area as regulated in the Yogyakarta regional regulation. The aim of this research is to analyze the actual requirements for obtaining an IMB and the requirements for constructing a building in a cultural heritage area. This research method is to use a normative juridical method, namely a method that focuses on the analysis of legal norms contained in statutory regulations, legal principles, legal theories related to this research. The results of this research are: 1. Obtain the correct procedures for obtaining a building construction permit in Yogyakarta. 2. Royal Apartments does not meet the requirements for constructing buildings in cultural heritage areas which are also regulated in the Yogyakarta Regional Regulation.